A DUAL-EDGED TRIGGERED EXPLICIT-PULSED LEVEL CONVERTING FLIP-FLOP WITH A WIDE OPERATION RANGE - Chen, Mei-Wei; Chang, Ming-Hung; Wu, Pei-Chen; Kuo, Yi-Ping; Yang, Chun-Lin; Chu, Yuan-Hua; Hwang, Wei (My University, 2013)
In a multiple supply voltage system, the level converters are inserted between two different voltage domains. However, those level converters may cause the propagation delays and power consumption. In order to eliminate the overhead of level conversion, a dual-edged triggered explicitpulsed level converting flip-flop (DETEP-LCFF) with a wide operation range is proposed. It is composed of a clock pulse generator and a modified differential cascode voltage switch with pass gate (DCVSPG) latch. The clock pulse generator has the symmetric pulse triggering time and holding period helping shorten the D-Q delay. By employed diode-connected PMOS transistors and two NMOS transistor stacked below the diode PMOS transistors, the proposed DETEP-LCFF can be operated from near-threshold region to superthreshold region. It is implemented in TSMC 65nm CMOS technology. It functions correctly across all process corners with a wide input voltage range, from 400mV to 1V. The proposed LCFF has a minimum D-Q delay of 781 ps, a setup time of 610ps, and a power dissipation of 2.3 mu W when the input voltage is OAV.